Tactical aspects of a national university taekwondo championship in relation to round and match outcome - Menescardi, C.; Lopez-Lopez, J. A.; Falcó, C.; Hernandez-Mendo, A.; Estevan, I. (The Journal of Strength and Conditioning Research, 2015)
The aims of this study were to analyze tactical behavior (direct attacks and indirect attacks, in addition to anticipatory, simultaneous, and posterior counterattacks) according to competition round and match, and to compare tactics of competitors (winners and nonwinners) in a university taekwondo championship. The analysis included 334 individual performances from 204 athletes over 169 bouts in the National University Championship. A 2-way repeated measure analysis of variance was conducted with "round" (at 3 levels: first, second, and third) as the within-subject factor and match outcome (at 2 levels: winning and nonwinning) as the between-subject factor. The results of this study show that tactical behavior patterns of winners and nonwinners differ. In addition, these differences vary over the course of a bout (p = 0.05). Winners perform fewer direct and indirect attacks than nonwinners perform, but execute more anticipatory, simultaneous, and posterior counterattacks. In terms of tactics in each round, there are more frequent direct and anticipatory actions in the third round than in earlier rounds (p = 0.05). Therefore, coaches should conduct tactical training for athletes in a variety of counterattacks, especially in the third round.